A Curriculum for Teaching Clinical Efficiency Focusing on Specific Communication Skills While Maximizing the Electronic Health Record - Kelly Skelly; Wendy Shen; Jason Wilbur; Kate Thoma; Jill Endres; Alison Lynch; Anne Gaglioti; Marcy Rosenbaum (Association of American Medical Colleges, 2020)
Introduction All physicians must learn comprehensive patient care delivery within the electronic health record (EHR). No studies have considered EHR communication training with an emphasis on clinical efficiency. This curriculum provides a method of teaching clinic efficiency while practicing effective patient communication in any EHR clinical situation. The target audience is resident physicians, fellow physicians, faculty physicians, and physician extenders practicing in a primary care setting where the EHR is present. Methods This curriculum of four separate workshops provides a structured EHR approach while addressing communication strategies for preclinical preparation, rapport building, encounter initiation, agenda setting, and visit closure. The curriculum contains interactive presentations, tools, and an evaluation survey. Presenting efficiency issues with the EHR using the ATTEND mnemonic and agenda setting allows documentation while practicing communication techniques that maximize efficiency. Results Postworkshop surveys revealed that participants felt the workshops were helpful (84%). One measurement of efficiency revealed improvement through decreased number of days to note completion after workshop participation. At the Program Directors Workshop, curriculum value was demonstrated by high attendance, with 94% feeling the workshops provided easily utilizable strategies. Discussion The curriculum utilized only the EPIC EHR but would be generalizable. Future directions could include measurement of effective communication and visit efficiency through direct observation and expanded EHR timing data.